2013
DOI: 10.1530/joe-13-0201
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation as a potential link between nonalcoholic fatty liver disease and insulin resistance

Abstract: Nonalcoholic fatty liver disease (NAFLD) has become a major health problem in developed countries. It has affected more than 30% of the general population and is commonly associated with insulin resistance, which is a major risk factor for the development of type 2 diabetes and a central feature of the metabolic syndrome. Furthermore, accumulating evidences reveal that NAFLD as well as insulin resistance is strongly related to inflammation. Cytokines and adipokines play a pivotal role in inflammatory processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
207
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 260 publications
(219 citation statements)
references
References 115 publications
6
207
1
5
Order By: Relevance
“…Epidemiologic studies have revealed a strong association between endometrial cancer and insulin resistance (IR) as well as inflammation (4)(5)(6)(7), and inflammation is one of the most significant clinical manifestations of IR (8). In agreement with this clinical finding, macrophage infiltration, a specific manifestation of chronic inflammation, was found to be positively correlated with development of many kinds of cancers, including endometrial cancer (9,10).…”
Section: Introductionmentioning
confidence: 79%
“…Epidemiologic studies have revealed a strong association between endometrial cancer and insulin resistance (IR) as well as inflammation (4)(5)(6)(7), and inflammation is one of the most significant clinical manifestations of IR (8). In agreement with this clinical finding, macrophage infiltration, a specific manifestation of chronic inflammation, was found to be positively correlated with development of many kinds of cancers, including endometrial cancer (9,10).…”
Section: Introductionmentioning
confidence: 79%
“…The increased lipid exposure in healthy volunteers induces hepatic accumulation of triglycerides, [12,15] which also involves an increase in the release of inflammatory cytokines such as tumor necrosis factor and interleukin-6. [16,17] Because an increase in these cytokines is associated with downregulation of P450 enzyme activity, [18] one may speculate that such an inflammatory response might be involved in the decreased activity of CYP3A4 and CYP2C19. In accordance, in vitro studies have also demonstrated reduced CYP3A4 activity in human steatotic livers.…”
Section: Discussionmentioning
confidence: 99%
“…Among metabolic alterations known in obesity, abnormal high levels of circulating cytokines activate the JNK pathway, which is considered as the molecular link between obesity and metabolic alterations (Solinas and Karin, 2010). For instance, IL-6 and TNFa, two proinflammatory cytokines present at high levels in obese patients (Asrih and Jornayvaz, 2013), have been shown to activate the JNK signaling pathway, leading to the development of insulin resistance (Hotamisligil et al, 1993;Spranger et al, 2003). Altogether, these studies suggest that the JNK pathway plays a major role in the development of MetS in obesity.…”
Section: Inflammation and Er Stress Induce Insulin Resistance In Metsmentioning
confidence: 99%